Technical aspect of hatchery management for mutiara catfish (Clarias sp.) at Balai Benih Ikan Lokal (BBI) Pontianak City - Nur Habibah; Uray Januardi; Wariah Wariah (PAKIS JOURNAL INSTITUTE, 2023)
Mutiara catfish is one of the most popular commodities for cultivation activities. This is because it grows quickly and is easy to cultivate. This fish is the result of breeding by the Sukamandi Fish Breeding Research Agency (BPPI). The aim of this research is to observe the technical aspects of pearl catfish hatchery management. The spawning process is carried out naturally and artificially. In this activity, the ratio of male to female parents is 1: 1. From the results of the frying carried out, it can be seen that the weight of eggs from natural spawning is lower than from artificial spawning. The two values are 100 g and 200 gr. Fecundity, or the number of eggs produced, also shows the same thing. With a fecundity value for artificial spawning of 43,200 eggs and artificial spawning of 70,000 eggs.